PENGARUH MODEL PEMBELAJARAN SELF ORGANIZED LEARNING ENVIRONMENT (SOLE) TERHADAP SIKAP ILMIAH DAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI KOLOID SMA/MA - Yoni Kurnia; Jaslin Ikhsan (Postgraduate, University of Mataram, 2023)
Education requires a learning model that involves technological developments to improve students' scientific attitudes and cognitive learning outcomes. One learning model that can be used to improve students' scientific attitudes and cognitive learning outcomes is the Self Organized Learning Environment (SOLE). This research aims to test whether there is an influence of the SOLE learning model on students' scientific attitudes and cognitive learning outcomes as well as the number of effective contributions made by the SOLE learning model on students' scientific attitudes and cognitive learning outcomes. This research is a quasi-experimental research. The sample in this research were students from two classes of XI Mipa at SMAN 2 Yogyakarta. The sampling technique in this research used cluster random sampling. Data collection techniques were carried out using questionnaires and observation sheets on students' scientific attitudes and test questions. The data analysis technique used is the Manova test and descriptive analysis. Based on the research results, the sig value was obtained. 0.00 < 0.005, which means that there is an influence of the SOLE learning model on students' scientific attitudes and cognitive learning outcomes with an effective contribution of 11.6% in the medium category. Meanwhile, the contribution for each variable, namely scientific attitudes, was 4.6% in the small category and cognitive learning outcomes were 7.7% in the small category.